The College Student-Athlete: Special Needs and Development Interventions--A Survey of the Literature - Whittemore, Wendy (My University, 1985)
Whittemore reviewed te literature on athlete development and transitions. She considered successful programs implemented at various institutions, especially for freshmen and some for seniors preparing for life after sport/college. She noted concerns with the limited access ahtletes have to support from trained counselors a their institutions, and testing opportunities for academic challenges and needs, and collaboration opportunities on campus.
Keywords: student development; academic predictors; academic support; transitions; models